Home vs. cross-border takeovers: Is there any difference in investor perception? - ATM Adnan (European Financial and Accounting Journal, 2018)
This paper attempts to portray the empirical difference in investors' perception towards the cross-border and domestic merger and acquisition (M&A) announcements of UK acquirer firms reflected through the significant abnormal stock return. The researcher conducts a short-run event study on the daily stock return of 100 UK bidding firms (50 involved in domestic and 50 involved in cross-border M&As between 2015 and 2016) to compare any significant abnormal returns (AAR and CAAR) around the event announcement period. National and international mergers and acquisitions have witnessed a considerable expansion globally, with the United Kingdom being one of the pioneers in the worldwide market for corporate domination. Research results exhibit that in domestic M&A bidding, firms experience a significant positive announcement return (CAAR) in the event window (t1 - t0) redolent to the positive expectation of investors from the M&A transaction. However, the post-announcement negative return concurrently proves the initial overreaction of investors and the semi-efficient market hypothesis. Foreign M&As result in an insignificant positive return (CAAR) in all the three event windows. There was existence of a positive trend in the cross-border pre-event return (AAR) indicative of narrow possibilities of insider trading or investors' optimistic anticipation, but this is not significantly conclusive.
Keywords: 650; Abnormal return; Cross-border; Domestic; Mergers and acquisitions; Shareholders